Short and Straightforward Enantioselective Synthesis of Both Enantiomers of Mequitazine through Iridium-Catalyzed Asymmetric Hydrogenation of a Nonfunctionalized Cyclic Enamine - Gauthier, Sébastien; Larquetoux, Laurent; Nicolas, Marc; Ayad, Tahar; Maillos, Philippe; Ratovelomanana-Vidal, Virginie (Synlett, 2014)
A short and straightforward asymmetric synthesis of both enantiomers of the antihistaminic drug mequitazine is reported. This atom-economical and attractive method features an iridium-catalyzed asymmetric hydrogenation of a nonfunctionalized cyclic enamine as a key step to install the C3-stereogenic center. After a full investigation of the effects of catalyst precursors, ligands, solvents, temperature, and hydrogen pressure, mequitazine (1) is obtained in good yield (up to 80%) and with acceptable enantiomeric excesses up to 47%.
Keywords: mequitazine; iridium; asymmetric catalysis; hydrogenation; enamine